Monetary Cross-Checking in Practice - Günther W. Beck; Robert C. M. Beyer; Markus Kontny; Volker Wieland (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Ever since the European Central Bank presented its monetary policy strategy on the basis of two pillars "economic" and "monetary" analysis with the latter being used as a cross-check of the first it has been criticized for giving too much importance to monetary aggregates. Opponents argue these aggregates are largely unrelated to monetary policy and provide little or no relevant information. Supporters have instead referred to the success of the Bundesbank in controlling inflation by using monetary targets during the 1970s and early 1980s. Furthermore, loose monetary conditions in the 2000s are viewed by many as a driver of excessive growth of credit and asset prices that set the stage for the global financial crisis. We use a formal characterization of monetary cross-checking and go on to study its role in policy practice empirically. Firstly, we derive historical measures of monetary conditions using this definition of cross-checking for Germany from the 1970s to 1998 and for the euro area since then. We investigate when monetary cross-checking would have called for significant adjustments in interest rate policy. Secondly, we test empirically whether interest rate policy responded to significant deviations of money. Such cross-checks induce a nonlinear shift in rates based on a threshold in terms of filtered money growth. Our estimates of threshold autoregressive models indicate that the behavior of the Bundesbank can well be described by a standard Taylor interest-rate rule augmented by a nonlinear component which induces an interest-rate adjustment when a filtered money growth measure exceeds an empirically specified threshold. Concerning the policy making of the ECB, we find supportive evidence for Trichet s(2008) claim of an interest-rate adjustment induced by a signal from monetary cross-checking at the end of 2004. However, our empirical results would have suggested an even larger (and earlier) response.
Keywords: C10; E41; E58; 330